Understanding sex a young person's guide - Guttmacher, Alan Frank 1898- (New York Harper & Row, 1970)
Describes the male and female reproductive organs and their functions and discusses such topics as masturbation, intercourse, venereal disease, and contraception.
Keywords: Sex instruction for youth; Sex instruction for youth